Multiscaling of lattice curvature on friction surfaces of metallic materials as a basis of their wear mechanism; Physical Mesomechanics; Vol. 20, iss. 1 - Panin V. E. Viktor Evgenyevich; Pinchuk V. G. Vyacheslav Grigorievich; Korotkevich S. V. Sergey Vasiljevich; Panin S. V. Sergey Viktorovich (2017, 2017)
Title screen